Comprehensive design and analysis of a cascade loop Resonant-Statefeedback control strategy for a Voltage Source Inverter (International Journal of Engineering and Computer Science, 2025)
This paper presents a Resonant-State Feedback cascade control strategy for a voltage source inverter (VSI), aimed at achieving complete controllability of the system. Specifically, a pole placement technique-based state feedback is utilized in the current loop, which facilitates comprehensive control over both current and voltage states, enhances system dynamics, and effectively rejects disturbances. A classical resonant controller is employed in the outer voltage loop to minimize steady-state error and compensate for harmonic distortion induced by the load. The proposed digital control strategy accounts for computational delays inherent in digital systems by integrating a phase delay compensator within the voltage loop. Simulation studies conducted using MATLAB demonstrate that the control system can effectively regulate output voltage, achieving Total Harmonic Distortion (THD) levels of only 1.21% and 2.31%, respectively, even under nonlinear load conditions. These results underscore the effectiveness of the proposed control strategy